Recent Trends and Impacts of Fisheries Exploitation on Mediterranean Stocks and Ecosystems - Colloca, Francesco; Scarcella, Giuseppe; Libralato, Simone (Frontiers in Marine Science, 2017)
This review focuses on the recent data on Mediterranean fishing fleets and landings, results from stock assessments and ecosystem models to provide an overview of the multiple impacts of fishing exploitation in the different Mediterranean geographical sub-areas (GSAs). A fleet of about 73.000 vessels is widespread along the Mediterranean coasts. Artisanal activities are predominant in South Mediterranean and in the eastern basin, while trawling features GSAs in the western basin and the Adriatic. The overall landings of fish, crustaceans and cephalopods, after peaking during mid ‘90s at about one million tons, declined at about 700.000 in 2013. However, while landings are declining in EU countries since the 90s, in non-EU a decreasing trend was observed only in the last 5-10 years. The current levels of fishing effort determine a general overexploitation status of commercial stocks with more than 90% of the stock assessed out of safe biological limits. Indicators obtained from available ecosystem models included primary production required to sustain fisheries (PPR), mean trophic level of the catch (mTLc), the loss in secondary production index (L index) and the probability of the ecosystem to be sustainably fished (psust). In areas exploited sustainably (e.g. Gulf of Gabes, Eastern Ionian and Aegean Sea) fishing pressure was characterized by either low number of vessels per unit of shelf area or the large prevalence of artisanal/small scale fisheries. Conversely, GSAs in Western and Adriatic showed very low ecosystem sustainability of fisheries that can be easily related with the high fishing pressure and the large proportion of overfished stocks obtained from single species assessments. We showed that the current knowledge on Mediterranean fisheries and ecosystems depict a worrisome picture where the effect of poorly regulated fisheries, in combination with the ongoing climate forcing and the rapid expansion of non-indigenous species, are rapidly changing the structure and functioning of the ecosystem with unpredictable effects on the goods and services provided. Although this would call for urgent conservation actions, the management system implemented in the region appears too slow and probably inadequate to protect biodiversity and secure fisheries resources for the future generations.